IMPLEMENTING THE MERIT SYSTEM THROUGH TALENT MANAGEMENT AS CAREER DEVELOPMENT BASIS - Ummu Azzizah; Laura Syahrul; Yulihasri (Journal Publicuho, 2024)
This study aims to determine antecedents of the low aspect career development for civil servant and the application of talent management strategies as a solution to career development issues. By using a qualitative method to executes semi-structure interview for 7 informants that responsible and have authorities to the civil servant career development. The collecting data also conducted through observation and documentation. Result of interviews show that six of ten indicators from career development aspects un-optimum implemented, such as job competency standards documents, availability of employee profiles based on talent or competency mapping, talent pool implementation, availability of succession plans, qualification and competency gap documents, and capacity building and competency development. Further, research findings show that the obstacles of career development aspects caused by six indicators such as bureaucratic politicization, lack of leadership commitment, un-optimum budget, and bad teamwork. The Talent management strategy states as comprehensive solution in establishing the basis for future civil servant career development.